Early English Translations of Grimm’s "Children and Household Tales" as Children’s Literature - Kiani, Isabel (Porównania, 2023)
The Children and Household Tales (Kinder- und Hausmärchen, KHM) by the Brothers Grimm are not only an integral part of German culture but have also become a global success over the last two centuries. Currently, the collections of the Grimm brothers include translations into over 100 languages, some of which were written during the lifetime of the Brothers Grimm. English editions in particular carry a considerable influence on the global reception of the tales, since most of the tales are received in a translation instead of the original language. However, many readers of the Grimms’ tales are not aware of this. It is often disregarded that a translation can rarely be described as identical to the original and is subject to different factors such as the translation tradition, the target culture, or the translator’s own ideas. The following essay investigates how and why the tales were edited in English translation to be modified as children’s literature.